TELAAH PENDIDIKAN KARAKTER DALAM BUKU TEKS BAHASA INDONESIA SD KURIKULUM MERDEKA - Ihsan Budi Satria; Siti Rochmiyati; Banun Havifah Cahyo Khosiyono (Universitas Sarjanawiyata Tamansiswa, 2023)
Study of Character Education in Indonesian Elementary School Textbooks Merdeka Curriculum. Basic Education Study Program Thesis Directorate of Postgraduate Graduate University Tamansiswa Yogyakarta 2023. This research includes (1) To describe the study of grade I Indonesian textbooks on the independent curriculum, (2) To describe the study of Grade II Indonesian textbooks on the independent curriculum, ( 3) To describe the study of grade IV elementary school Indonesian textbooks on the independent curriculum. This type of research is descriptive qualitative research. Data collection techniques using the reading and writing technique were carried out by reading, understanding the contents of the book, studying the contents of the book, and noting the character education contained in the Indonesian language textbooks in the Merdeka Curriculum Elementary School. This study also used data analysis techniques from data reduction, data display, and data verification by validating the data using focus group discussions (FGD). The results of the study are (1) dimensions of faith, fear of the one and only God and noble character found in personal morals, morals towards humans, morals towards nature and national morals, but no state morals are found in class I books and no religious morals are found in class books I, II, and IV. Whereas (2) the global diversity dimension, (3) the cooperative dimension, (4) the independent dimension, (5) the critical reasoning dimension, and (6) the creative dimension have been found in class I, II, and IV books.